The effects of macroeconomics variables on stock index: Kuala Lumpur Composite Index - Abu Zarim, Noraznida (Faculty of Business and Management, 2014)
There are only a few research papers that had been conducted in Malaysia based on the previous studies that focusing on the topic which is effect of macroeconomic variables on stock market. There are no specific macroeconomic variables that had been stated give the effect toward stock market because each of the research studies is using different variables. Therefore, the independent variables used in this study are specific to exchange rate, interest rate, crude oil price, consumer price index and money supply while the dependent variable is Malaysian stock market return (KLCI). The main objective of this research study is to investigate whether there is a relationship between selected macroeconomic variables towards Malaysian stock market return. The data collection for this research study is from secondary data which is from Jan 1999 until December 2013 based on monthly data. All the data were find by using datastream that provided by UITM. The study employed a time series multiple regression analysis which is using E-view software. This software is used to test and analyze the data that had been collected.